Physical Activity Levels Based on Indonesian Population Characteristics: Evidence from the Indonesian Family Life Survey-5 (Althea Medical Journal, 2026)
Background:  According to the World Health Organization, approximately 80% of the global population is physically inactive. Sedentary behavior is a major contributor to the increasing risk of chronic diseases. This study aimed to describe physical activity levels among the Indonesian population and examine their associations with sociodemographic and lifestyle factors. Methods:  This cross-sectional study was conducted from March to November 2024 using secondary data from the Indonesian Family Life Survey-5 (IFLS-5). Variables analyzed included age, gender, ethnicity, marital status, body mass index (BMI), perceived health status, occupation, education level, residence, sleep quality, smoking status, and physical activity level. A total of 4,156 respondents were included. Associations between population characteristics and physical activity levels were examined using the chi-square test.Results:  Nearly half of the respondents engaged in light physical activity (47.8%), followed by moderate (28.0%) and vigorous physical activity (24.2%). Significant associations were found between physical activity levels and age (p=0.015), gender (p
Keywords: IFLS-5; lifestyle factors; physical activity; sedentary behavior